Water Savings and ‘Innovation’ Zoysiagrass Quality in Response to Irrigation Strategy - Manoj Chhetri; Jack Fry; Megan Kennelly; Dale Bremer; Jared Hoyle (Kansas Agricultural Experiment Station Research Reports, 2020)
Performance of ‘Innovation’ zoysiagrass was evaluated under four irrigation regimes: a) routine irrigation (1.2 inches weekly); b) evapotranspiration (ET)-based irrigation (60% of estimated ET); c) soil water sensor (SWS)-based irrigation; and d) no irrigation. The SWS-based irrigation method reduced water application by 72% and 56%, respectively, compared to routine or ET-based irrigation. Visual turf quality of turf receiving SWS-based irrigation remained above the minimal acceptable level throughout the study. Innovation zoysiagrass sustained acceptable quality for more than 21 days with no irrigation, and nonirrigated turf recovered fully within four weeks after irrigation treatments ceased and turf was well irrigated. Soil water sensors are useful for saving irrigation water, and Innovation zoysiagrass demonstrated good drought tolerance and recovery after drought.
Keywords: drought tolerance; soil-moisture sensor; evapotranspiration